2003
DOI: 10.1097/01.gme.0000055486.06076.db
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of ovarian stromal Doppler signals in postmenopausal women receiving hormone replacement therapy

Abstract: There was a significant increase in ovarian stromal flow indices after 3 months of treatment in the HRT group, but not in the controls. Monitoring the ovarian flow changes by three-dimensional power Doppler may be of clinical importance when HRT is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The vascular indices, including VI, FI and VFI, all decrease significantly in the order of premenopause, perimenopause, and then postmenopause. However, this situation is reversed after 3 months of continuousecombined hormone replacement therapy [9]. All 3D power Doppler indices of ovarian stromal flow show a significant increase after treatment.…”
Section: Ovarymentioning
confidence: 91%
“…The vascular indices, including VI, FI and VFI, all decrease significantly in the order of premenopause, perimenopause, and then postmenopause. However, this situation is reversed after 3 months of continuousecombined hormone replacement therapy [9]. All 3D power Doppler indices of ovarian stromal flow show a significant increase after treatment.…”
Section: Ovarymentioning
confidence: 91%
“…The clinical and economic burden associated with diabetes mellitus and its management remains an enduring challenge to the healthcare community [ 1 ]. It is well known that menopause status affects estrogen level [ 2 ] which plays an important role in regulating glucose homeostasis [ 3 , 4 ] and fat metabolism [ 5 , 6 ]. In menopause, a decrease in estrogen level caused by the depletion of ovarian function results in an increase in abdominal fat [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the sex hormones in females are contributed regulating the lipid metabolism (Nikolic et al, 2016) and the homeostasis of glucose ) Hao et al,2015). The epidemiological studies demonstrated the status of menopause was influenced by the levels of estrogen (Pan et al, 2003) and is related to osteoporosis, urogenital atrophy, sexual dysfunction, psychiatric disorders, metabolic disorders, cardiovascular disease ,and obesity (Lobo et al, 2014;Utian and Wood ,2013;Archer et al,2015). T2DM consider a multigenic metabolic disturbance that happens in the various age categories as a result of environmental and genetic factors (Malecki and Klupa,2005).…”
Section: Introductionmentioning
confidence: 99%